EFEKTIVITAS PROGRAM BANTUAN SOSIAL DALAM PENGURANGAN KEMISKINAN PEDESAAN (STUDI KASUS DESA TANAH MERAH, SIAK HULU) - Irwan Gesmi (Ensiklopedia of Journal, 2026)
Rural poverty remains a complex and multidimensional development challenge in Indonesia. The government has implemented various social assistance programs as social protection instruments to mitigate the impacts of poverty, particularly among poor and vulnerable households. This study aims to analyze the effectiveness of social assistance programs in reducing rural poverty in Tanah Merah Village, Siak Hulu District. A qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation involving 20 informants, consisting of program beneficiaries, village officials, and community leaders. The findings indicate that 45% of respondents used social assistance to meet food needs, 25% for education-related expenses, and 20% for health needs, while only 10% utilized the assistance for productive economic activities. Furthermore, the utilization pattern of social assistance was predominantly oriented toward daily consumption (70%), whereas only 30% was allocated to productive purposes. In terms of targeting accuracy, 60% of beneficiaries were appropriately targeted, while 25% experienced inclusion errors and 15% exclusion errors. This study concludes that social assistance programs are effective in maintaining household consumption among poor households; however, their effectiveness in promoting sustainable poverty reduction remains limited. Therefore, stronger integration between social assistance programs, economic empowerment initiatives, and improved governance mechanisms is required to enhance the long-term impact of rural poverty reduction.Keywords: social assistance programs, rural poverty, program effectiveness, social protection, economic empowerment